2n-3=8n+9

Simple and best practice solution for 2n-3=8n+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n-3=8n+9 equation:


Simplifying
2n + -3 = 8n + 9

Reorder the terms:
-3 + 2n = 8n + 9

Reorder the terms:
-3 + 2n = 9 + 8n

Solving
-3 + 2n = 9 + 8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-8n' to each side of the equation.
-3 + 2n + -8n = 9 + 8n + -8n

Combine like terms: 2n + -8n = -6n
-3 + -6n = 9 + 8n + -8n

Combine like terms: 8n + -8n = 0
-3 + -6n = 9 + 0
-3 + -6n = 9

Add '3' to each side of the equation.
-3 + 3 + -6n = 9 + 3

Combine like terms: -3 + 3 = 0
0 + -6n = 9 + 3
-6n = 9 + 3

Combine like terms: 9 + 3 = 12
-6n = 12

Divide each side by '-6'.
n = -2

Simplifying
n = -2

See similar equations:

| 7x=90+22 | | (4x+18)=(16x-12) | | 18-2(4x-1)=12 | | (4t+16)+(5t-21)=180 | | 7+2(3x-1)=8x-3(2x+5) | | -3x-2y=17 | | y-32=-10 | | p^2-2pq+q^2=0 | | x^2-6x^2-9= | | 30-6x=6-3x | | Y=X^2+9x+18 | | -16x^2-60x+6=0 | | x^2+16x-78=0 | | 18s^3=-50s | | 2x-y+17=0 | | 5-5x=0 | | x^2+10x-119=0 | | 5-9=3 | | -5+(-15d+1)=2(7d-16)-d | | 21x-5-16x+2=17x-9-12x+15 | | 6x-16=-96 | | 3(c+5)= | | 4r=-28 | | 23b-19b= | | (10x+3)=(15x-7) | | 15x+14y+27x=0 | | 14x-7=12x+3 | | 9y+11y= | | y=100 | | (4t+16)=(5t-21) | | a-3.5=19.5 | | x=4-2x |

Equations solver categories